The Influence of Hope and Meaning in Life as Predictors of Flourishing Among Higher Education Students - Krismona, Elwas Berdha; Asfarina, Lilla Maturizka Ayu; Suryawati, Citra Tectona; Syahril, M. Fiqri; Latifah, Anisah Muflihatul; Oktafia, Nurul (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
The study aims to see the influence of hope and the meaning of life on the flourishing of students majoring in education. Flourishing is an individual's positive mental condition to balance negative and positive aspects and recognize their strengths. For students majoring in education, flourishing is needed so that they are ready to have motivation and commitment as educators. The study uses a quantitative approach with a correlational method. The multiple linear regression test used to see the influence of hope and meaning of life on student flourishing shows a significant value of 0.000, which means that hope and meaning of life influence student flourishing.